A nationwide post-marketing survey of knowledge, attitude and practice toward human papillomavirus vaccine in general population: Implications for vaccine roll-out in mainland China. Issue 1 (3rd January 2021) - Hu, Shangying; Xu, Xiaoqian; Zhang, Yanyang; Liu, Yawen; Yang, Chunxia; Wang, Yueyun; Wang, Yan; Yu, Yanqin; Hong, Ying; Zhang, Xingxing; Bian, Rui; Cao, Xian; et al.
Highlights: HPV vaccine awareness and knowledge is limited in general population. HPV vaccine uptake is still low in China despite high willingness to be vaccinated. Safety, lack of knowledge and high price are main obstacles to be vaccinated. Safety concern, lack of knowledge, and high price of HPV vaccines are main obstacles for general population to get vaccinated. Abstract: Background: Human papillomavirus (HPV) vaccine has been increasingly discussed in mainland China since its first approval in 2016. To date, nearly all studies assessing HPV vaccine perceptions and attitudes were implemented during pre-licensure period. Therefore, the nationwide post-marketing survey was conducted to update knowledge, attitudes and practice on HPV vaccine among general population in mainland China. Methods: Participants aged 18–45 years living in mainland China were recruited in April 2019 by multi-stage non-randomized sampling. Sociodemographic factors, HPV and HPV vaccine related awareness, knowledge, attitudes, vaccine uptake and potential obstacles were assessed in questionnaires. Bivariate analysis and multivariate regression were used to identify disparity among subgroups with different sociodemographic characteristics. Results: 4, 000 women (32.1 ± 7.81y) and 1, 000 men (31.8 ± 7.96y) were included in final analysis. Less than one third of participants had heard of HPV (female: 31%; male: 22%) and HPV vaccine (female: 34%; male: 23%). Knowledge score was also unfavorable on HPV (female: 3 out of 13; male: 1.8 out of 13) and HPV vaccine (female: 3 out of 6; male: 2 out of 5). Only 3% females had been vaccinated three years after HPV licensure in China, although willingness to get vaccinated among those unvaccinated were high (mean willingness score ± SD: female: 3.3 ± 0.97; male: 3.0 ± 0.98). Industry of employment and household income were the major factors related to awareness and knowledge of vaccine, whereas HPV and HPV vaccine awareness were key influential factors for willingness. The main obstacles of vaccination were safety concerns, lack of knowledge, and high price of HPV vaccines. Conclusions: Findings highlight a lack of vaccine awareness, knowledge, and poor uptake in mainland China and underscore the necessity of health education campaigns. The identified priority groups, contents to be delivered and practical obstacles could furthermore provide insight into health education to reduce disparities and accelerate HPV vaccine roll-out in China.